A call for action: The impact of business model innovation on business ecosystems, society and planet. Issue 6 (December 2022) - Snihur, Yuliya; Bocken, Nancy
Abstract: The impact of business model innovation (BMI) on business ecosystems, society, and planet is of growing theoretical and practical importance for strategic management. Increasing sustainability pressures warrant a better understanding of the impact of companies' BMI through a more comprehensive analysis of innovation and its consequences. We discuss four foci of innovation (BMI, sustainable BMI, ecosystem innovation, and sustainable ecosystem innovation) to broaden the conceptualization of innovation and its economic, societal, and natural environmental impacts. We call for scholarship examining the impact of BMI to advance knowledge through research on value destruction and the dynamics of BMI over time.